Reconstruction of Heel: Options and Strategies (Bangladesh Journal of Plastic Surgery, 2010)
Soft tissue loss at the weight bearing part of heel is frequently caused by trauma, infection, tumor and burn. Reconstruction becomes a challenge due to limitation of available similar or near similar tissues. Sensation of weight bearing heel is an important consideration prior to reconstruction, also the intact Posterior Tibial arterial blood flow, which becomes the dominant artery for the sole of the foot. We have done heel reconstruction of 30 patients with the Medial Plantar Island flap and 50 patients with Superficial Sural Island flap. Results were very much encouraging in terms of flap survival, durability of coverage and functional outcome. Twenty nine cases of Medial Plantar Island flap survived with excellent weight-bearing function. Among the Medial Plantar Island flap group one flap was lost due to vascular insufficiency in a diabetic patient. All the 50 cases (100%) of Superficial Sural Island flap survived without any flap loss. These flaps need about two years time for adaptive changes to become a smooth weight bearing heel. During this period the reconstructed heel needs to be supported by heel pad or modified shoes. Our study has shown that Medial Plantar Island flap and Superficial Sural Island flap are the two armamentarium for reconstruction of the weight-bearing heel in about all cases of heel defects with excellent to better reconstructive and functional outcome.DOI: http://dx.doi.org/10.3329/bdjps.v1i1.6487Bangladesh Journal of Plastic Surgery (2010) Vol. 1 (1) pp.14-18